THE EFFECT OF REMUNERATION AND LEADERSHIP GROWING ON THE ACCREDITATION PERFORMANCE OF DEPARTEMENT AT UIN SUMATERA UTARA MEDAN - Khairina Tambunan; Isnaini Harahap (IAIN Lhokseumawe, 2022)
Higher education accreditation aims as an evaluation of achievement so that the results will be used to improve and improve the previous standards. With the statue of UIN Sumatera Utara Medan as a Public Service Agency, remuneration is something that affects the accreditation performance of its department, as well as leadership growth. This research aims to see the effect of remuneration and leadership growth on the accreditation performance of department at the UIN Sumatera Utara Medan, either partially or simultaneously. With 61 departments owned, it can be taken a sample of 52 respondents. As a result, the remuneration and leadership growth have a significant effect on the accreditation performance of department at the UIN Sumatera Utara Medan, either partially or simultaneously. The coefficient of determination obtained shows that remuneration and leadership growth can explain the effect of 43.4%%. The findings obtained are that the department has problems in its accreditation performance. However, many departmental managers can overcome this with various efforts made. Recommendations for the availability of accreditation data with a one-door system, increasing the ability of departmental managers in carrying out their main tasks, the availability of funds and the availability of sufficient human resources.